Breastfeeding counseling in rooming-in care: a scoping review - Michele Curcino Cavalcanti; Elisa da Conceição Rodrigues; Cynthya Viana de Resende; Monika Wernet; Karine Emanuelle Peixoto Oliveira da Silva; Mariana Torreglosa Ruiz (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to map evidence available in the literature on breastfeeding counseling in rooming-in. Methods: a scoping review, following the stages recommended by the JBI to answer the review question: what evidence is available in the literature on breastfeeding counseling during the binomial’s hospitalization in rooming-in? Searches were conducted in the PubMed/MEDLINE, LILACS, Scopus, EMBASE, Web of Science, CINAHL, PsycInfo and CAPES Dissertation and Theses Catalogue databases, using the descriptors “Counseling”, “Breast Feeding”, “Rooming-in Care” and “Mother-Child Binomial” and their synonyms, without time or language limitations. Results: seven studies, published between 1999 and 2020, predominantly in English, were included in the analysis. Conclusions: there was a shortage of studies on the subject and the positive effects on reducing the belief of insufficient milk and singularities.